Media representations of Venezuelan migration in Portugal and Argentina: Between exceptionalism and a returning diaspora - Padilla, B.; França, T.; Melella, C. (Migration Studies, 2024)
Since the Venezuelan humanitarian crisis, Venezuelan migration to Portugal and Argentina has increased significantly, generating media reactions. Even if media discourses about immigrants in general tend to be negative, Venezuelans seem to be an exception, as the image portrayed tends to be positive, associated either with their highly skilled profile or with their European ancestors. By applying mass-media critical discourse analysis, this article analyses dominant media representations of Venezuelan migrants in Portugal and Argentina between 2015 and 2019, and shows how discourses represent them according to the leading policies that frame migrations in each context of destination. In Portugal, Venezuelans are perceived as Luso-descendants returning home, so they are not specifically targeted by immigration policies but are rather ambiguously included in diaspora policies while abroad; even upon return, they are considered national citizens. In Argentina, Venezuelans are seen as talented migrants who bring along qualifications and entrepreneurship capacity to the country, thus deserving exceptional treatment and solidarity due to the humanitarian crisis caused by the Chavez–Maduro regime. Both examples illustrate how positive media images carry different connotations depending on ideological and policy discourses shaped by local–global historical processes and contexts.